Low oocyte quality related with the aging ewes - Ali, Abbas Musa; Hatif, Saad Akram (The Iraqi Journal of Veterinary Medicine, 2013)
This study was conducted to know the effect of ewe age on oocyte quality as well as the relationsbetween oocyte viability and normal uterine condition. Eighty three (83) reproductive systems ofnon-pregnant ewes were collected from Al-shulla abattoir. The Total oocytes were aspirated from right ovaries reached 61.45% and 38.55% from left ovaries. Immediately after aspiration, the oocytes were examined by light microscopic and conceded as mature if surrounded completely with cumulus oopherus. While the stained oocytes by trypan blue were conceded as dead oocytes and excluded. According to ewes age the oocytes were classified into (3) groups, the first group ranged between 1-2 years, second group 3-6 years and the third group over 6 years. The total oocyte collection fromthese groups was 20, 23, 40 oocyte. The results indicated that 14 oocytes (70%), 17(73.91%) and 10(25%) from groups 1, 2, and 3 with cumulus cells, respectively. While the total live oocyte reached to 60. Normal endometrium was observed in 90%, 95% and 80%for 1,2and 3 groups respectively. It was concluded from this study that aged ewes showed low quality oocyte with infertile endometrium.